Anti-ischemic effect of ethyl acetate extract of Aquilaria crassna by attenuation of p38-MAPK activation - Chanyatip Suwannasing,, Nitchawat Paiyabhroma,, Sarawut Kumphune, (Journal of Applied Pharmaceutical Science)
Aquilaria crassna has been traditionally used in traditional Thai herbal formulation for treatment of fainting by targeting the cardiovascular system. This study was aimed to investigate the ex vivo effect of ethyl acetate extract of Aquilaria crassna (A.E) in isolated mouse heart, subjected to ischemia/reperfusion, and its mechanism on p38 MAPK activation. The hearts from ICR mouse, age 6-8 weeks, were retrograde-perfused on Langendorff perfusion system. The hearts were randomized to 5-mg/ml A.E for 30 min prior to 30 min of global ischemia, followed by 2 h of reperfusion. After reperfusion, all hearts were stained with 1% triphenyltetrazolium chloride (TTC) and sliced. The TTC-negative infarction volume was expressed as a percentage of heart volume. The p38-MAPK activation was performed by Western blot analysis. The results showed that global ischemia was significantly increased the infarct volume. Pre-treatment with 5-mg/ml of A.E. for 30 min prior to global ischemia significantly reduced infarct volume (47.61±3.68 % versus 21.08± 8.16 %, p
Keywords: Ischemic Heart Disease, Aquilaria crassna, myocardial ischemia/reperfusion, infarct volume, p38 MAPK